2016
DOI: 10.5796/electrochemistry.84.882
|View full text |Cite
|
Sign up to set email alerts
|

Keggin-type Polyoxometalates as Bidirectional Redox Mediators for Rechargeable Batteries

Abstract: Keggin-type polyoxometalates (POMs), which possess multiple redox centers, were investigated as bidirectional redox mediators in rechargeable batteries. A series of POMs have been synthesized and employed in sulfur electrodes where neither the active material nor the discharge product were electrically conductive. POMs were found to have multiple redox potentials covering the range of the equilibrium potentials of the redox reactions of sulfur, which consequently facilitated both charge and discharge reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Moreover, each tungsten (W) atom of Keggin-type KPW is in the highest valence state (VI), which endows phosphotungstate with a unique multielectron storage capacity and robust redox ability. The KPW cluster and its corresponding reduced KPW species can reversibly store or transfer multiple electrons during reactions. , Subsequently, X-ray photoelectron spectroscopy (XPS) was further employed to investigate the interaction between Li 2 S 4 and KPW clusters (Figure S5c). Comparing the pristine KPW cluster, we observed a slight broadening of the W 6+ 4f doublet and a shift toward lower binding energies (BEs) of 37.1 and 34.8 eV for the W 5+ 4f 5/2 and W 5+ 4f 7/2 peaks, respectively, upon the adsorption of Li 2 S 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, each tungsten (W) atom of Keggin-type KPW is in the highest valence state (VI), which endows phosphotungstate with a unique multielectron storage capacity and robust redox ability. The KPW cluster and its corresponding reduced KPW species can reversibly store or transfer multiple electrons during reactions. , Subsequently, X-ray photoelectron spectroscopy (XPS) was further employed to investigate the interaction between Li 2 S 4 and KPW clusters (Figure S5c). Comparing the pristine KPW cluster, we observed a slight broadening of the W 6+ 4f doublet and a shift toward lower binding energies (BEs) of 37.1 and 34.8 eV for the W 5+ 4f 5/2 and W 5+ 4f 7/2 peaks, respectively, upon the adsorption of Li 2 S 4 .…”
Section: Resultsmentioning
confidence: 99%
“…The KPW cluster and its corresponding reduced KPW species can reversibly store or transfer multiple electrons during reactions. 50,55 Subsequently, X-ray photoelectron spectroscopy (XPS) was further employed to investigate the interaction between Li 2 S 4 and KPW clusters (Figure S5c). Comparing the pristine KPW cluster, we observed a slight broadening of the This indicates the oxidation of Li 2 S 4 into long-chain polysulfide (Figure S5d).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…15–19 In recent years, the application of POMs has been extended to LSB systems to conquer the shuttle effect. According to previous reports, 20,21 it can be concluded that W-containing POMs present appropriate redox potentials that cover the range of equilibrium potentials of sulfur redox reactions, and thus are more conducive to enhancing the electrochemical property of LSBs. Notably, when bulk POMs are utilized as the sulfur-fixing materials, the inevitable agglomeration will bury the effective active sites of POMs so as to limit their adsorption or catalysis function for LiPSs.…”
Section: Introductionmentioning
confidence: 80%
“…This ceramic membrane also completely separates the anode and cathode sides, allowing the use of different electrolyte compositions on each side 6 . Carefully selected electrolytes can suppress excessive reactions on the metal, and this allows the uses of mediators 810 and aqueous electrolytes on the cathode 1123 . However, thick ceramic plates are needed to compensate for their mechanical fragility, which adds significant volume and mass to the cell and lowers the specific energy of the Li-air batteries.…”
Section: Introductionmentioning
confidence: 99%